Client Satisfaction in 'Ex - servicemen Contributory Health Scheme (ECHS) Polyclinic': An Experience from India - Phuyal, Naveen; Jindal YSM, Ashok Kumar; Mukherji, Sandip (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Client or patient satisfaction is considered as one of the desired outcomes of health care and it is directly related to utilization of health services. We aim to study the client satisfaction regarding services in a Health Insurance Scheme Polyclinic for Veterans. Methods: This observational and analytical cross-sectional study was conducted at an Ex-servicemen Contributory Health Scheme (ECHS) Polyclinic, India. A structured questionnaire was used for the study for which a total of 400 clients were interviewed. Results: Overall, the respondents thought that the services provided by the polyclinic were good. None of the respondents rated the polyclinic to be poor, majority of them (68.8%) rated it to be good, 13.8% rated it to be excellent and 17.5% were just satisfied with the services at the polyclinic. Conclusion: The ultimate aim of ECHS is to ensure that the veterans, who have given their best years of life in the service of the nation in extremely hostile conditions, get the best possible preventive, promotive and curative care when they need it most. ECHS of this kind with improvements sounds relevant in context of Nepalese armed forces as well.